Model pembelajaran game based learning dalam pembelajaran fisika - Fernando, Yusdi; Eka Fitria, Tazha; Zaturrahmi, Zaturrahmi (UIN Alauddin Makassar, 2024)
This research aims to analyze the use of technology in the form of game based learning in learning which includes: (1) problems that cause the use of game based learning in learning, (2) variables that are influenced by the use of game based learning in learning. This research method is a literature review with 10 articles in journals. Data collection is carried out by collecting similar scientific articles and then analyzing them. The results of this literature review research show that the main problem that causes the use of game based learning in learning is that the material taught is too difficult and uninteresting so that one cannot concentrate during learning. Furthermore, the variable that greatly influences the use of game-based learning is effectiveness.